2021
DOI: 10.1016/j.celrep.2021.109003
|View full text |Cite
|
Sign up to set email alerts
|

Phasic Off responses of auditory cortex underlie perception of sound duration

Abstract: Highlights d A1 neurons exhibit transient Off responses time-locked to the termination of sound d Precisely timed excitatory followed by inhibitory input underlies the Off response d Weakening A1 Off responses reduces perception of sound duration, and vice versa d Creating artificial phasic On-and Off-like activity in A1 allows duration perception

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 72 publications
4
24
0
1
Order By: Relevance
“…Another approach to understanding the behavioral role of auditory offset responses could be to study where AAF is projecting and what could be the use of offset responses in these areas. It was recently shown that A1 transient offset responses to noise stimulation underlie the perception of sound duration ( Li et al, 2021 ). As AAF supplies ∼45% of the cortical input to A1 ( Lee and Winer, 2008 ) and the modulation of acoustic information between A1 and AAF in the cat’s ACx was shown to be dominated by a unidirectional AAF to A1 pathway ( Carrasco and Lomber, 2009 ), it would be interesting to understand if A1 offset responses originate from AAF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another approach to understanding the behavioral role of auditory offset responses could be to study where AAF is projecting and what could be the use of offset responses in these areas. It was recently shown that A1 transient offset responses to noise stimulation underlie the perception of sound duration ( Li et al, 2021 ). As AAF supplies ∼45% of the cortical input to A1 ( Lee and Winer, 2008 ) and the modulation of acoustic information between A1 and AAF in the cat’s ACx was shown to be dominated by a unidirectional AAF to A1 pathway ( Carrasco and Lomber, 2009 ), it would be interesting to understand if A1 offset responses originate from AAF.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, Weible et al demonstrated that the cortical postgap neural activity in mice is related to detecting brief gaps in noise ( Weible et al, 2014b ). Recently, it was shown that A1 transient offset responses contribute critically to encoding and perceiving sound duration ( Li et al, 2021 ). Whether the increased neuronal activity of sound offset responses accounts for other perceptual skills is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Male and female wild type (C57BL/6J) and transgenic (PV-Cre, Ai14 and Ai32) mice aged 2-3 months were used. The method was described in the previous studies [30][31][32] . Mice were anesthetized with isoflurane (1.5%, v/v) and a head post for fixation was mounted on top of the skull with dental cement.…”
Section: In Vivo Single Cell Recordingmentioning
confidence: 99%
“…Mice were anesthetized with isoflurane (1.5%, v/v) and a head post for fixation was mounted on top of the skull with dental cement. Skull over the A1 was cleaned and protected from being covered by dental cement as we described previously [30][31][32] . Afterward the mouse was injected subcutaneously with 0.1 mg kg-1 buprenorphine and returned to its home cage.…”
Section: In Vivo Single Cell Recordingmentioning
confidence: 99%
“…По-видимому, такая высокая вариабельность латентных периодов ответов нейронов слуховой коры может отражать повышение вклада торможения в обработку звуковой информации при переходе от стволового уровня слуховой системы к корковому, а также усложнение самой временной обработки звуков. С учетом результатов ранее выполненных исследований, свидетельствующих, что в системе «стволовые центры слуха -слуховая кора» претерпевают изменения все основные частотно-временные характеристики активности нейронов (Egorova 2005;Egorova et al 2020;Gaucher et al 2020;Khorunzhii, Egorova 2015;Li et al 2021), представляется очевидным, что на уровне нейронов слуховой коры изменяется взаимодействие процессов возбуждения и торможения, изменяется вклад нейронов в различные аспекты кодирования звука, а также усиливается их вовлеченность в интегративные процессы более высокого порядка. Установление механизмов этих процессов остается актуальным вопросом будущих исследований.…”
Section: результаты и обсуждениеunclassified